Analisis Yuridis Perbuatan Wanprestasi Dengan Cara Tidak Menandatangani Akta Jual Beli Yang Dibuat Di Hadapan Pejabat Pembuat Akta Tanah - Samion Ginting; Rosnidar Sembiring (CV. KAMPUS AKADEMIK PUBLISING, 2023)
The occurrence of a default (broken promise/default) is a situation where the debtor is unwilling or unable to fulfill the promises stated in the loan agreement. The trigger for a debtor to default can be natural (beyond the debtor's ability and will) or due to the debtor's good intentions. This research aims to analyze the legal status of Deeds of Sale and Purchase in the sale and purchase of land that apply in Indonesia, to analyze the criteria for breach of contract by not signing, and acts of default in Deeds of Sale and Purchase agreements made before the Official Land Deed Maker in Medan District Court Decision Number 96 /Pdt.G/2022/PN Mdn. The research was carried out using legal research, namely normative juridical which is descriptive analytical in nature, which is research that aims to describe a situation or symptom or to determine whether there is a relationship between a symptom and another symptom. The data collection techniques used were library research and document study. Based on the research results, the legal position of the Deed of Sale and Purchase in the sale and purchase of land is that it is only obligatory, meaning that the new sale and purchase agreement lays down reciprocal rights and obligations between both parties. If the sale and purchase is canceled due to an act of breach of contract in the agreement, then based on the judge's legal considerations in the case of the decision, the judge grants the plaintiff's claim, and states that the sale and purchase transaction between the plaintiff as buyer and the defendant as seller is due to the evidence held by the plaintiff. authentic evidence that has legal force, namely having a Certificate of Ownership